Warthin's Tumors and Their Relationship to Lung Cancer. (2nd January 2015) - White, Christine Klimowicz; Williams, Kimberly A.; Rodriguez-Figueroa, Jorge; Langer, Corey J.
<x xml:space="preserve">Abstract</x> Warthin's tumors (WT) are frequently encountered in clinical practice and can be easily mis-identified. To date, there has been no proven association between WT and lung cancer. A retrospective chart review was conducted of records from 2008 to 2013 in the University of Pennsylvania Health System. Nineteen percent of patients had a diagnosis of lung cancer, compared to the general patient population, where 7.62% of males and 6.26% of females have a lifetime risk of developing lung cancer. Patients with WT are at heightened risk of lung malignancy; detection of WT may lead to earlier diagnosis of lung cancer.